PENGARUH LINGKUNGAN KERJA, FASILITAS KERJA DAN LATAR BELAKANG PENDIDIKAN TERHADAP PENGGUNAAN SISTEM INFORMASI AKUNTANSI DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI - Mustari, Wilda; Wawo, Andi; Fadhilatunisa, Della (ISAFIR: Islamic Accounting and Finance Review, 2023)
This study aims to determine how the influence of the work environment, work facilities and educational background on the use of accounting information systems with organizational culture as a moderating variable. This study uses a quantitative method with a causality approach. This research was conducted at PT Semen Tonasa, Pangkep Regency. Methods of data collection is done by using a questionnaire. The number of respondents used in this study was 35 people. The results of this study indicate that the work environment, work facilities and educational background have a positive and significant impact on the use of accounting information systems. Organizational culture moderates the influence of work environment and educational background on the use of accounting information systems. Organizational culture does not moderate and weaken the effect of work facilities on the use of accounting information systems.